Salivary irisin in relation to recurrent aphthous ulcerand weight status in Diyala city/Iraq - Taher, Aya K; Radhi , Nada JMH (Journal of Baghdad College of Dentistry, 2024)
Background: Recurrent aphthous stomatitis remains the most common ulcerative disease of the oral mucosa that exists as painfull round shallow ulcers with a well-defined erythematous margin and a yellowish grey pseudomembranous centre. Salivary irisin is an identified adipomyokine and research has revealed that it has an anti-inflammatory effect and is a novel myokine; it is synthesized in skeletal muscle and adipose tissue. The aim of the present study was to evaluate the relation of salivary irisin to recurrent aphthous ulcers and weight status in Diyala City / Iraq. Materials and methods: A cross-sectional comparative study was carried out during the period from the end of December (2021) until the end of March (2022). The total sample size composed of all patients attending a specialised dental center in Ba’aquba / Diyala governorate with recurrent aphthous ulcers of both gender and ages ranged from 20-30 years (100 patients consider the study group) assessed according to the directions suggested by the WHO (1997) and compared to the control group free from this lesion (100 patients consider the control group) matching in age and sex. The weight status was assessed using the digital weight scale. The sub samples of 45 from each study and the control group were selected to analyse salivary irisin. The description of data, presentation, and analysis process is carried out through the use of the SPSS package (SPSS version 22, Chicago, Illinois, USA). For the quantitative variable mean, the standard deviation (SD) was used. Frequency and percentage are used for the qualitative variable. The independent sample T test was used for the difference between the two groups. Pearson’s correlation was used for the linear correlation between two quantitative variables. Results: The highest percentage of recurrent aphthous ulcer was found in the lower lip. The mean value of irisin was higher among the study group than in the control group. The mean value of the body mass index among the control group was higher than that of the study group. When correlating the body mass index with salivary irisin, it is a positive weak not significant correlation. Conclusions: This study concluded that there is an elevated level of irisin among recurrent aphthous ulcers, in addition to that, the recurrent aphthous ulcer decreases the body mass index.